THE RELIABILITY AND LIMITATIONS OF GOOGLE TRANSLATE: A BILINGUAL, BIDIRECTIONAL AND GENRE-BASED EVALUATION - Roig Allué, Blanca (Entreculturas. Revista de traducción y comunicación intercultural, 2017)
The popularity of machine translation systems (or CAT, computer-assisted translation), which enable their users to obtain automatically generated translations of any text, has been increasing ever since they were created. One of the most widely used machine translation is Google Translate, a statistical system whose performance is the object of study of this paper. In order to evaluate its reliability, a small-scale study has been carried out in which translations of tourist texts and football match reports published online generated by the tool have been analysed, and the most representative mistakes found in terms of frequency have been classified at a lexicogrammatical, syntactic, pragmatic and punctuation level. Based on these findings, the main linguistic limitations of Google Translate have been established. It is worth highlighting the fact that three crucial variables have intervened in the corpus compilation, namely language (English/Spanish), direction of the translation (English into Spanish and vice versa) and genre of the texts (tourist and sports).